Critical Materials:Underlying Causes and Sustainable Mitigation Strategies - S Erik Offerman (World Scientific Series in Current Energy Issues, 2019)
This book covers a new frontier of research in Critical Materials that provides insight in terms of the possible sustainable mitigation strategies, the complexity, broadness and multi-disciplinarity of the subject. By exploring in both "systems view" and "in-depth materials view" in light of the circular economy, this book tackles the problem of sustainable usage of materials that is closely intertwined with the energy issue and climate change. Topics covered include: geopolitics of materials, the energy-materials nexus, definitions of the criticality of materials, circular product design, the development of alternative materials (substitution), sustainable mining and recycling.